No, it's not C.
f(-3) means substitute x = -3 to the function:
f(x) = x^2 - 4x + 3
f(-3) = (-3)^2 - 4(-3) + 3
f(-3) = 9 + 12 + 3
f(-3) = ?
Given the function rule f(x)=x^2-4x+3, what is the output of f(-3)?
A- 24
B- 21
C- 0***
D- -3
11 answers
So wouldn't it be 24? A?
that 9 should be negative right?
wait nevermind calculater being stupid
f(x) = x^2 - 4x + 3
f(-3) = (-3)^2 - 4(-3) + 3
f(-3) = 9 + 12 + 3
f(-3) = 21 + 3
f(-3) = 24
If you wanted to you could divide 24 by -3 to find f because f times -3 is 24. So...
24 / -3 = -8
f = -8?
I have no clue
f(-3) = (-3)^2 - 4(-3) + 3
f(-3) = 9 + 12 + 3
f(-3) = 21 + 3
f(-3) = 24
If you wanted to you could divide 24 by -3 to find f because f times -3 is 24. So...
24 / -3 = -8
f = -8?
I have no clue
The answer is A 24
ty @? and @Slushie
Given the function rule f(x) = x² – 4x + 3, what is the output of f(–2)?
To find out the output of f(-2), we need to substitute -2 for x in the equation f(x) = x² – 4x + 3 and simplify.
f(-2) = (-2)² – 4(-2) + 3
f(-2) = 4 + 8 + 3
f(-2) = 15
Therefore, the output of f(-2) is 15.
f(-2) = (-2)² – 4(-2) + 3
f(-2) = 4 + 8 + 3
f(-2) = 15
Therefore, the output of f(-2) is 15.
Given the function rule f(x) = x² – 4x + 3, what is the output of f(–3)
To find the output of f(-3), we need to substitute -3 for x in the equation f(x) = x² – 4x + 3 and simplify.
f(-3) = (-3)² – 4(-3) + 3
f(-3) = 9 + 12 + 3
f(-3) = 24
Therefore, the output of f(-3) is 24.
f(-3) = (-3)² – 4(-3) + 3
f(-3) = 9 + 12 + 3
f(-3) = 24
Therefore, the output of f(-3) is 24.